Fungal Resistance of Canvas and Dluwang in Humid Tropics - Septiyana Baroroh; Lontar Sauh Tantarlia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Canvas and dluwang are cellulose-based painting supports that differ in material composition and surface characteristics, resulting in different susceptibilities to fungal biodeterioration. This study evaluated fungal colonization dynamics on canvas and dluwang using Trichoderma sp., a cellulolytic fungus commonly associated with deterioration of organic cultural materials. Sterile canvas and dluwang were placed on Potato Dextrose Agar (PDA) colonized by Trichoderma sp. and incubated at room temperature under a relative humidity of >70% for 28 days. Fungal growth was assessed every seven days using a semi-quantitative surface coverage categorization (0%, <25%, 25–50%, 50–75%, >75%). The results revealed different colonization patterns between the two materials. Dluwang showed rapid colonization, increasing from 25–50% at day 7 to >75% by day 14 and remaining fully colonized thereafter. In contrast, canvas remained at <25% colonization throughout the incubation period. These findings highlight the importance of considering material characteristics and resistance to fungal biodeterioration in preventive conservation and support the development of effective conservation strategies for organic artistic supports in tropical environments.